ความชุก และปัจจัยที่มีอิทธิพลต่อพฤติกรรมการสูบบุหรี่ไฟฟ้าของเด็กและเยาวชนไทย: Prevalence and Factors Influencing E-cigarette Smoking Behavior Among Thai Children and Youth - รัตพร, วันเฉลิม (วารสารวิชาการกรมสนับสนุนบริการสุขภาพ, 2025)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาความชุก และปัจจัยที่มีอิทธิพลต่อพฤติกรรมการสูบบุหรี่ไฟฟ้าของเด็ก และเยาวชนไทย เป็นการศึกษาเชิงวิเคราะห์แบบภาคตัดขวาง ใช้ข้อมูลทุติยภูมิ จากฐานข้อมูลการเฝ้าระวังพฤติกรรม การสูบบุหรี่ไฟฟ้าคนไทย ปี พ.ศ. 2567 ของกองสุขศึกษา กรมสนับสนุนบริการสุขภาพ กลุ่มตัวอย่าง จำนวน 7,900 คน สุ่มกลุ่มตัวอย่างด้วยวิธีแบบแบ่งชั้นภูมิ วิเคราะห์ข้อมูลเชิงพรรณนาด้วยร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน วิเคราะห์อิทธิพลของตัวแปรด้วยการถดถอยลอจิสติกเชิงพหุ ผลการวิจัย พบว่า เด็กและเยาวชนไทยสูบบุหรี่ไฟฟ้าร้อยละ 26.14 ปัจจัยส????ำคัญที่มีอิทธิพลต่อพฤติกรรมการสูบบุหรี่ไฟฟ้า ได้แก่ การสูบบุหรี่มวน (AOR=4.52;95%CI:3.56,5.73) การมีทัศนคติต่ำกว่าระดับดี (AOR=3.65;95%CI:3.16,4.22) การดื่มน้ำกระท่อม (AOR=2.96;95%CI:2.32,3.78) การดื่มแอลกอฮอล์ (AOR=2.40;95%CI:2.08,2.76) ความเครียด (AOR=1.32; 95%CI:1.15,1.53) สถานภาพสมรสบิดามารดา (AOR=1.26; 95%CI:1.11,1.44) ประสบการณ์เห็นคนมีชื่อเสียงสูบบุหรี่ไฟฟ้า (AOR=1.20; 95%CI:1.04,1.36) การเข้าถึงผลิตภัณฑ์บุหรี่ไฟฟ้า (AOR=1.24; 95%CI: 1.07,1.43) การมีเพื่อน แฟน สูบบุหรี่ไฟฟ้า (AOR=2.71; 95%CI:2.29,3.21) และการถูกชักชวนให้สูบบุหรี่ไฟฟ้า (AOR=1.72;95%CI:1.50,1.98) ดังนั้น หน่วยงานที่เกี่ยวข้องควรมีการจัดการปัจจัยเสี่ยงพฤติกรรมการสูบบุหรี่ไฟฟ้าแบบบูรณาการ ทั้งปัจจัยนำ ปัจจัยเอื้อ และปัจจัยเสริม โดยดำเนินการในกลุ่มเด็กและเยาวชนที่มีพฤติกรรมเสี่ยงอื่น (เช่น สูบบุหรี่มวน ดื่มน้ำกระท่อม ดื่มแอลกอฮอล์) บิดาและมารดาแยกทางกัน สมรรถนะทางวิชาการไม่ดี ศึกษาในสถาบันการศึกษานอกระบบ และการศึกษาตามอัธยาศัย เป็นลำดับแรก This study aimed to examine the prevalence and influential factors associated with e-cigarette use among Thai children and youth. A cross-sectional analytical design was employed using secondary data from the 2024 Thai E-Cigarette Surveillance Database, conducted by the Health Education Division, Department of Health Service Support. The sample size was 7,900 participants, and the sample was selected using the stratified random sampling method. Descriptive statistics were analyzed using percentages, means, and standard deviations. Multiple logistic regression was used to assess the influence of predictive factors. The findings revealed that 26.14% of Thai children and youth used e-cigarettes. The factors influencing e-cigarette use included: smoking conventional cigarettes (AOR=4.52; 95%CI:3.56,5.73), having attitudes below the good level (AOR=3.65; 95%CI:3.16,4.22), consuming kratom (AOR=2.96; 95%CI:2.32,3.78), alcohol consumption (AOR=2.40; 95%CI:2.08,2.76), experiencing stress (AOR=1.32; 95%CI:1.15,1.53), parents’ marital status (AOR=1.26; 95%CI:1.11,1.44), exposure to celebrities using e-cigarettes (AOR=1.20; 95%CI:1.04,1.36), accessibility to e-cigarette products (AOR=1.24; 95%CI: 1.07,1.43), having friends or partners who use e-cigarettes (AOR=2.71;95%CI:2.29,3.21), and being persuaded to use e-cigarettes (AOR=1.72; 95%CI:1.50,1.98). Therefore, relevant agencies should implement integrated risk management strategies targeting predisposing, enabling, and reinforcing factors. Priority should be given to youth exhibiting other risk behaviors (e.g., cigarette smoking, kratom consumption, alcohol drinking), those with separated parents, poor academic performance, and those enrolled in non-formal or informal education systems.